2019
DOI: 10.1093/cid/ciz524
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Ertapenem Prophylaxis for Carriers of Extended-spectrum β-Lactamase–producing Enterobacteriaceae Undergoing Colorectal Surgery

Abstract: Background Carriers of extended-spectrum β-lactamase–producing Enterobacteriaceae (ESBL-PE) who receive cephalosporin-based prophylaxis have twice the risk of surgical site infection (SSI) following colorectal surgery as noncarriers. We tested whether ESBL-PE screening and personalized prophylaxis with ertapenem reduces SSI risk among carriers. Methods We conducted a prospective nonrandomized, nonblinded, interventional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…A recent study suggested that personalized ertapenem prophylaxis for enteric ESBL-producing Enterobacteriaceae carrier can reduce SSI among patients who underwent colorectal surgery. 12 In this study, given that majority of patients had superficial SSIs, we found no association between carbapenem use as surgical prophylaxis and reduction in SSIs. Our study has a few notable limitations.…”
Section: Discussionmentioning
confidence: 48%
“…A recent study suggested that personalized ertapenem prophylaxis for enteric ESBL-producing Enterobacteriaceae carrier can reduce SSI among patients who underwent colorectal surgery. 12 In this study, given that majority of patients had superficial SSIs, we found no association between carbapenem use as surgical prophylaxis and reduction in SSIs. Our study has a few notable limitations.…”
Section: Discussionmentioning
confidence: 48%
“…We recently reported high rates of ESBL-PE carriage among colorectal surgery candidates, and showed that ESBL-PE carriers receiving cephalosporin-based prophylaxis were twice as likely to develop SSI as non-carriers [7]. We also demonstrated that ESBL-PE carriers undergoing colorectal surgery had significantly lower SSI rates when given ertapenem prophylaxis (15.8%) compared to cephalosporin-based prophylaxis (22.7%) [8].…”
Section: Introductionmentioning
confidence: 64%
“…This single-centre nested study was part of the Resistance in Gram-Negative Organisms: Studying Intervention Strategies (R-GNOSIS) project conducted in 2012e2017, in which patients undergoing colorectal surgery were screened for ESBL-PE carriage [7,8].…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…1,2 Screening for ESBL-pE and personalized ertapenem use was associated with reduction in the incidence of SSIs caused by ESBL-pE. 3 Despite the potential benefit, screening all patients for ESBL-pE carriage may be considered an excess cost in resourcelimited settings. Selective screening for high-risk groups with ESBL-pE carriage may be an alternative approach to surveillance screening and antimicrobial stewardship.…”
Section: Appendix B Examples Of Tweets Labeled As Possible Misuse Anmentioning
confidence: 99%
“…Clostridioides difficile-associated diarrhea (CDAD) is the most frequently reported healthcare-associated illness in the United States, with an annual economic burden >$1 billion and up to 9% mortality, and critically ill trauma patients may be uniquely at risk. [1][2][3][4] Military trauma patients have multiple CDAD risk factors, including frequent broad-spectrum antimicrobial exposure, transient immunosuppression, and challenges related to infection control in the deployed environment and along the evacuation chain. We describe the epidemiology of wounded military personnel diagnosed with CDAD.…”
Section: Appendix B Examples Of Tweets Labeled As Possible Misuse Anmentioning
confidence: 99%